Peran Kecemasan sebagai Faktor Pemicu Kekambuhan Stomatitis Aphtosa Reccurent - Audita Astri Wardhany; Sartari Entin Yuletnawati (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Background: Recurrent Aphthous Stomatitis (RAS) is one of the most frequently encountered oral mucosal conditions. Although RAS has been extensively considered clinically and through research, ulcer occurrence remains unavoidable, and most treatment approaches are primarily symptomatic. Objective: To identify anxiety as a predisposing factor in patients with minor RAS. Case Report: A 24-year-old female patient presented to Soelastri Dental and Oral Hospital with a complaint of an ulcer on the right upper lip. The patient reported pain and a burning sensation for the past four days. The pain worsened when consuming hot food or beverages. The patient had experienced similar episodes previously but had never sought treatment for this condition. Intraoral examination revealed a single shallow ulcer with an oval shape, regular margins, a yellowish-white base surrounded by an erythematous halo, measuring 3 × 2 mm on the right upper lip, and was symptomatic. Case Management: The treatment provided focused primarily on Communication, Information, and Education (CIE). The patient was informed about the predisposing factor experienced, which may contribute to the occurrence of RAS, namely anxiety. The patient also received education regarding maintaining oral hygiene, consuming fruits and vegetables, increasing water intake, eating more regularly, attending a follow-up visit seven days after treatment, and managing anxiety. Conclusion: In this case, RAS management was focused on eliminating predisposing factors, particularly anxiety, which was strongly suspected to be the triggering factor for minor RAS in this patient.